Effects of sarang semut (Myrmecodia Pendens Merr. & Perry) extracts on Enterococcus faecalis sensitivity - Cut Soraya; Hendra Dian Adhyta Dharsono; Dudi Aripin; Mieke H Satari; Dikdik Kurnia; Danny Hilmanto (Dental Journal (Majalah Kedokteran Gigi), 2016)
Background: Enterococcus faecalis (E. faecalis) is a gram positive oral pathogen that reported at the main agent infection of endodontic treatment. Its activities are influenced by the virulence factors facilitating the interaction process between agents with host cells. Like aggregation substance, cytolysin, extracellular superoxide, gelatinase, hyaluronidase, sex pheromones, and surface adhesions molecules. Plant extracts are reported as the material antibacterial as well as E. faecalis in pathogenesis of endodontic infections. Purpose: Purpose of this study was to analyse of sarang semut extracts (Myrmecodia Pendens Merr. & Perry) towards sensitivity of E. faecalis. Method: This research used the methanol extract of sarang semut, E. faecalis ATCC 29212, and fosfomycin also chlorhexidine as the positive controls. Whereas, Bradford protein method was measured the concentration of the surface protein of E. faecalis and active component of the sarang semut extract. Result: Generally, the sarang semut extract possessed low sensitivity toward E. faecalis (≤ 13 mm), but on the concentrations of 100 µg/ml and 75 µg/ml better than inhibition of other concentrations, round 10.6-11.6 (mm). Specifically, on 100 µg/ml has indicator the minimal bactericidal concentration (MBC) on E. faecalis. Whereas minimal inhibition concentration (MIC) on the concentration of 3,125 µg/ml. Conclusion: Based on MBC and MIC assay, the extract of sarang semut has potential effects to adherence growth of E. faecalis, mainly on the highest concentration 100 µg/ml also MIC on 3,125 µg/ ml.